Urban pollution greatly enhances formation of natural aerosols over the Amazon rainforest - Shrivastava, Manish K.; Andreae, Meinrat O.; Artaxo, Paulo; Barbosa, H. M. J.; Berg, Larry K.; Brito, Joel F.; Ching, Joseph; Easter, Richard C.; Fan, J.; Fast, Jerome D.; Feng, Zhe; Fuentes, José D.; et al. (Nature Communications, 2019)
One of the least understood aspects in atmospheric chemistry is how urban emissions influence the formation of natural organic aerosols, which affect Earth’s energy budget. The Amazon rainforest, during its wet season, is one of the few remaining places on Earth where atmospheric chemistry transitions between preindustrial and urban-influenced conditions. Here, we integrate insights from several laboratory measurements and simulate the formation of secondary organic aerosols (SOA) in the Amazon using a high-resolution chemical transport model. Simulations show that emissions of nitrogen-oxides from Manaus, a city of ~2 million people, greatly enhance production of biogenic SOA by 60–200% on average with peak enhancements of 400%, through the increased oxidation of gas-phase organic carbon emitted by the forests. Simulated enhancements agree with aircraft measurements, and are much larger than those reported over other locations. The implication is that increasing anthropogenic emissions in the future might substantially enhance biogenic SOA in pristine locations like the Amazon. © 2019, This is a U.S. government work and not under copyright protection in the U.S.; foreign copyright protection may apply.
Keywords: Hydroxyl Radical; Isoprene; Nitrogen Oxide; Organic Carbon; Ozone; Peroxy Radical; Aerosol; Airborne Survey; Anthropogenic Source; Atmospheric Chemistry; Biogenic Emission; Energy Balance; Nitrogen Oxides; Organic Carbon; Oxidation; Pristine Environment; Rainforest; Urban Pollution; Aircraft; Amazonas; Carbon Footprint; Gas; Oxidation; Pollution; Rainforest; Secondary Organic Aerosol; Simulation; Urban Area; Amazonas; Manaus